2016
DOI: 10.18052/www.scipress.com/ijppe.2.30
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Chemical Composition, Characterization and Anti-Bacterial Activity of Acridine Diglycoside from <i>Moringa olifera</i>

Abstract: Abstract. Moringa olifera (drumstick tree) is a medicinal plant commonly used in phytomedicine to cure and prevent diseases in Nigeria. The ethanolic extract of the leave sample showed alkaloid {(9.66 ± 0.20) %}, phenols {(0.75 ± 0.22) %}, flavonoids {(6.86 ± 0.20) %}, saponines {(8.46 ± 0.10) %}, and tannins {(1.10 ± 0.20) %}. The plant also contains nutritional nutrients such as ash {(6.08 ± 0.02) %}, protein {(23.65 ± 0.12)%}, carbohydrates {(57.01 ± 0.01)%}, fats {(2.43 ± 0.01) %}, crude fibre {(6.02 ± 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…42 The Agricultural Health Study demonstrated that exposure to certain OPs, such as malathion and terbufos, was significantly associated with an increased risk for aggressive prostate cancer. 43,44 OPs like malathion have been linked to an increased risk of thyroid cancer and a decreased risk of non-Hodgkin lymphoma. 45 Chem.…”
Section: Classification and Properties Of Pesticidesmentioning
confidence: 99%
“…42 The Agricultural Health Study demonstrated that exposure to certain OPs, such as malathion and terbufos, was significantly associated with an increased risk for aggressive prostate cancer. 43,44 OPs like malathion have been linked to an increased risk of thyroid cancer and a decreased risk of non-Hodgkin lymphoma. 45 Chem.…”
Section: Classification and Properties Of Pesticidesmentioning
confidence: 99%